Numbers 3 : Infinity - Ward, Rachel 1964- (Chicken House, 2011)
Adam, Sarah and little Mia are living together, struggling with the fame of seeing numbers - the dates when people will die. But something is about to tear them apart. During The Chaos, Mia swapped her number for another. Mia's powerful new ability is highly desirable. Ruthless people are hunting her down. Everyone wants to live for ever..
Forts. von: Numbers: The chaos
Keywords: Psychic ability / Juvenile fiction; Young adult fiction; Weibliche Jugend; Außersinnliche Wahrnehmung; Großbritannien; Jugendbuch